Okay, here we have this:
Considering the provided information, we are going to find the requested equation of the parabola, so we obtain the following:
According to the information given by substituting in the form of the parabola we have the following equation:
![(x-2)^2=8(y-2)](https://img.qammunity.org/2023/formulas/mathematics/college/gdd9cajwykay1mei5biv8n2ju4u9xhh4e6.png)
Let's solve for y:
![\begin{gathered} y-2=((x-2)^2)/(8) \\ y-2=(x^2-4x+4)/(8) \\ y=(1)/(8)x^2-(1)/(2)x+(1)/(2)+2 \\ y=(1)/(8)x^2-(1)/(2)x+(5)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qh015pkl5g5sw1ymeie51kb1e72l78tyiu.png)
Finally we obtain that the correct answer is the option D.